2022
DOI: 10.1002/1873-3468.14355
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between autophagy and phytohormone signaling pathways in plants

Abstract: Autophagy is a conserved recycling process with important functions in plant growth, development, and stress responses. Phytohormones also play key roles in the regulation of some of the same processes. Increasing evidence indicates that a close relationship exists between autophagy and phytohormone signaling pathways, and the mechanisms of interaction between these pathways have begun to be revealed. Here, we review recent advances in our understanding of how autophagy regulates hormone signaling and, convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 152 publications
0
4
0
Order By: Relevance
“…Initially, it was assumed that ethylene and autophagy are not linked based on the lack of leaf senescence recovery phenotype in Arabidopsis plants deficient in both autophagy and Ethylene-Insensitive 2 ( EIN2) genes ( atg5ein2-1 or atg2ein2-1 double mutants; Yoshimoto et al, 2009). However, several studies later suggested that crosstalk between ethylene and autophagy may exist (Liao et al, 2022). First, the transcript abundance of many ethylene biosynthesis and some ethylene-signaling genes was higher in atg5 and atg9 mutants than in WT ( Col-0 ) Arabidopsis plants (Masclaux-Daubresse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was assumed that ethylene and autophagy are not linked based on the lack of leaf senescence recovery phenotype in Arabidopsis plants deficient in both autophagy and Ethylene-Insensitive 2 ( EIN2) genes ( atg5ein2-1 or atg2ein2-1 double mutants; Yoshimoto et al, 2009). However, several studies later suggested that crosstalk between ethylene and autophagy may exist (Liao et al, 2022). First, the transcript abundance of many ethylene biosynthesis and some ethylene-signaling genes was higher in atg5 and atg9 mutants than in WT ( Col-0 ) Arabidopsis plants (Masclaux-Daubresse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an evolutionarily highly conserved cyclic process that plays a major role in plant growth, development, and stress response [11]. The process of autophagosome formation involves several steps, including signal transduction (induction), isolation membrane formation (nucleation), isolation membrane elongation (elongation), autophagosome completion and transport (maturation), autophagosome-vacuole coupling and fusion (fusion), cargo degradation (degradation), and recycling [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cargoes including single macromolecules, large macromolecular complexes such as ribosomes and proteasomes, protein aggregates, damaged or whole organelles, and even invading pathogens can be eliminated through autophagy in bulk or selectively ( Liu and Bassham, 2012 ; Marshall and Vierstra, 2018 ). This autophagic process is critical for removing non-functional molecules within the cell and replenishing the nutrient sources for new growth, and it is also important for regulating specific biological processes or signaling pathways by selectively degrading specific cargoes ( Zhou et al, 2014 ; Nolan et al, 2017 ; Zhuang et al, 2018 ; Xia et al, 2020 ; Lin et al, 2021 ; Luo et al, 2021 ; Wang et al, 2021 ; Liao et al, 2022 ). Thus, autophagy plays important roles in plant growth and development and stress responses to facilitate plant tolerance and survival under unfavorable conditions ( Marshall and Vierstra, 2018 ).…”
Section: Introductionmentioning
confidence: 99%